2011
DOI: 10.3892/or.2011.1219
|View full text |Cite
|
Sign up to set email alerts
|

Impact of MET amplification on gastric cancer: Possible roles as a novel prognostic marker and a potential therapeutic target

Abstract: Abstract.Identification of critical genes which play pivotal roles in controlling tumor growth and survival will establish the basis for developing therapeutic targets. With the aim of establishing personalized medicine for treatment of solid tumors, we focused on MET amplification in gastric cancer patients, given the extreme sensitivity to c-Met inhibitor in MET amplified gastric cancer cell lines. We tested MET amplification and activation of c-Met in various gastric cancer cell lines and tissue samples fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 15 publications
3
60
1
Order By: Relevance
“…Gene amplification has been found to be significantly related to distant metastasis and tumor stage [12,39] . On copy number assay using reverse transcription polymerase chain reaction (RT-PCR), MET gene amplification was observed in 1.5% to 30% of tumors, although the definition of MET amplification somewhat differed among studies [15,18,[40][41][42] . In a study using single nucleotide polymorphism array, MET amplification was detected in 3% to 4% of patients [43,44] .…”
Section: Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gene amplification has been found to be significantly related to distant metastasis and tumor stage [12,39] . On copy number assay using reverse transcription polymerase chain reaction (RT-PCR), MET gene amplification was observed in 1.5% to 30% of tumors, although the definition of MET amplification somewhat differed among studies [15,18,[40][41][42] . In a study using single nucleotide polymorphism array, MET amplification was detected in 3% to 4% of patients [43,44] .…”
Section: Gene Expressionmentioning
confidence: 99%
“…Wang et al [43] reported that MET amplification was found in 7% (3 of 41) of intestinal type cancers, but not in other types. In many studies using FISH or RT-PCR, patients with MET-amplified tumors had significantly poorer survival than those with non-amplified tumors [12,15,18,32,39,41,42] . Only a Japanese study, with the lowest incidence of gene amplification, reported no relation of MET amplification to survival or any clinicopathological characteristic [40] .…”
Section: Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oncogenic activation of MET promotes cell proliferation, survival, migration, angiogenesis and apoptosis inhibition (Birchmeier et al 2003). Recently, several studies have shown the MET gene amplification is one of the causes of MET overexpression in GC; however, the frequency of MET amplification is various among previous studies (Lee et al 2011(Lee et al , 2012Huang and Chuang 2013;Kawakami et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of MET has been related to tumor stage and clinical outcome [67]. With the advent of MET inhibitors, the interest in this molecule had a revival, and a very recent large study conducted in Korea demonstrated that MET was amplified in 21% of GC and related to poor patient survival [68]. …”
Section: Molecular Mechanisms Of Gastric Carcinogenesismentioning
confidence: 99%